Jogos Digitais Sérios usados para o Exercício de Habilidades do Pensamento Computacional em Crianças com Transtorno do Espectro Autista - Malpartida, Katherin Felipa Carhuaz; Rodrigues, Kamila Rios da Hora (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2024: Proceedings of the 30th Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2024.242211, 2024)
Computational Thinking (CT) is a reasoning process focused on solving problems, promoting the development of cognitive skills. Serious games can contribute to exercise these skills, as they are playful and adaptable tools for different audiences. This paper presents the design and evaluation of a medium-fidelity serious digital game prototype designed to help improve the cognitive skills of children with Autism Spectrum Disorder (ASD), based on the fundamental principles of PC. The first phase of the game design was completed and evaluated by Special Education professionals from a partner institution. The observations and feedback collected are being discussed with the development and research teams to implement the functional version of the game.